Vehicle fuel consumption and emission modelling: an in-depth literature review - Faris, Waleed Fekry; Rakha, Hesham; Kafafy, Raed Ismail; Mohammed Idres, Moumen; Elmoselhy, Salah (Inderscience Enterprises Ltd., 2011)
Modelling of vehicle fuel consumption and emissions has emerged as an effective tool to help develop and assess vehicle technologies and to help predict vehicle fuel consumption and emissions. A review to identify the current state-of-the-art on vehicle fuel consumption and emissions modelling is elucidated. This review categorises vehicle fuel consumption and emissions models into five classifications. The relevant main models to each of these classifications are presented. These models are then compared with regard to assumptions, limitations, merits, drawbacks, characteristic parameters, data collection techniques, accuracy, and relevance to road traffic. The study demonstrates that the trends of vehicle fuel consumption and emissions provided by current models generally do satisfactorily replicate field data trends. In addition, the paper demonstrates that mesoscopic models, empirical models, mean value-based models, and quasi dimensional models strike a balance between accuracy and simplicity and thus are very suitable for transportation and control applications. The study shows as well that no one model as yet fully meets the needs of transportation applications.